Efforts To Improve Student Assertive Behavior In Learning Through Classical Services With Psikodrama Techniques (UNP Laboratory Development Middle School) - Yiyit Hentika; Neviyarni Neviyarni (Jurnal Neo Konseling, 2020)
Assertive behavior is positive personal development including honest (straightforward) behavior, direct and respectful expression of thoughts, feelings and desires by considering the feelings and rights of others (Ribha 2017). However, the reality in the field is found in many students who have low assertive behavior, especially in the field of learning, such as not being open in learning, easily anxious in facing exams, having strong principles in learning and not easily influenced. Then it will have an impact on the learning process that is not optimal and students do not have psotif developments in learning so it needs an effort to improve students' assertive behavior in learning. Many things can be done to improve students' assertive behavior in learning one of them with psychodrama techniques. This study aims to: (1) test students' assertive behavior in learning before being given classical service treatment with psychodrama techniques, (2) testing students' assertive behavior in learning after being given classical service treatment with psychodrama techniques, (3) differences in students' assertive behavior in learning with psychodrama techniques before and after the classical service treatment was given with psychodrama techniques.This research uses a pre-experimental type of experimental approach using the one group pretest-posttest design. The sample in this study was a seventh grade UNP Laboratory Development Middle School student C. The instrument used was a questionnaire about students' assertive behavior in learning. The data collected was analyzed using the Wilcoxon Signed Rank test formula with the help of the Statistical Product and Service Solution (SPSS) version 20 program.The results showed that classical services with psychodrama techniques can improve students' assertive behavior in learning with 79% pretest results in the low category and posttest increases to 68% with high categories.